The Combined Application of Surface Floating Wetlands and Bottom Anaerobic to Remediate AMD-Contaminated Lakes - Tianling Fu; Yonggui Wu; Hu Wang; Kaiju Chen; Yan Zeng; Zhongzheng Wen; Zhengyan Ran; Li He (Journal of Chemistry)
Acid mine drainage (AMD) causes environmental pollution that affects many countries with historic or current mining industries. The eco-remediation system (RW) which combined surface floating wetlands and bottom anaerobic sediments (SFW-BAS) was selected for AMD-contaminated lakes (AMDW). Meanwhile, AMDW and nature aquatic ecosystems (NW) were set as the control groups, respectively. The parameters, including pH, Eh, Fe, Mn, SO42−, and the degradation rate of the native dominant plant litter were investigated to assess the effects of remediation. The results showed that the average of pH, Eh, and EC, was 2.73, 484.08 mv, and 2395.33 μs·cm−1, respectively. The average content of SO42−, Fe, Mn, Cu, Zn, and Pb was 2190 mg·L−1, 40.2 mg·L−1, 4.6 mg·L−1, 249.2 μg·L−1, 1563 μg·L−1, and 112.9 μg·L−1, respectively. The degradation rate of plant litters in AMDW ranged from 14.5% to 22.6%. However, RW ultimately improved the water quality and the degradation of litters. RW has a good effect on buffering the acidity, ranging from 3.96 to 7.41. The pH of RW (6.14) is close to that of NW (7.41). The average content of SO42−, Fe, Mn, Cu, Zn, and Pb was 2071 mg·L−1, 3.4 mg·L−1, 2.4 mg·L−1, 85.3 μg·L−1, 607.4 μg·L−1, and 47.8 μg·L−1, respectively, which showed good pollutant removal performance. The degradation rate of plant litters in RW ranged from 27.8% to 32.6%. Therefore, RW can be used to remediate AMDW.